Implementasi Nilai-nilai Aswaja Dalam Kehidupan : Studi Kasus di Desa Trimulyo - Nuraini, Septi; Ehwanudin, Ehwanudin; Arifin, M. Zaenal (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
This study aims to examine the implementation of Aswaja (Ahlussunnah wal Jamaah) values in the daily life of the Trimulyo village community. Trimulyo is a predominantly Muslim village whose residents have long embraced Aswaja teachings as a foundation for both social and religious life. Employing a qualitative field research approach with a case study method, data were collected through interviews, observations, and documentation. The findings reveal that Aswaja values are practiced in tangible ways across various aspects of community life. Socially, the community upholds the principles of mutual cooperation (gotong royong), solidarity, and interfaith as well as interethnic tolerance. Religiously, residents regularly perform congregational prayers and actively participate in religious assemblies such as yasinan and sholawatan, which reinforce a moderate understanding of Islam. This study contributes to the discourse on how moderate Islamic teachings can be contextualized within rural communities to foster social harmony and religious coexistence.